2020
DOI: 10.21009/parameter.321.04
|View full text |Cite
|
Sign up to set email alerts
|

Model Konseptual Media Motion Graphic Interaktif Matematika Untuk Siswa Kelas v Sekolah Dasar

Abstract: The purpose of this research is to find a conceptual model as a basic in developing a learning media Mathematics of Scale material using motion graphic media. The development model used in this research is Hannapin and Peck's model which is consists of three stages, namely requirements analysis, design, and development or implementation. This research was conducted at SDN Karanggan 01 Gunung Putri, Bogor towards fifth grade students of elementary schools. The results of the product feasibility trial show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The research results from [43] showed that learning tools with problemposing approaches were effective to be applied in scale learning in the fifth-grade elementary school students. Research results from [44] showed that motion graphic media was effective in the learning process. In addition, the results of research from [45] showed that the use of a contextual approach in learning could improve the mathematical representation skills of students with high, medium, and low categories compared to conventional approaches.…”
Section: Resultsmentioning
confidence: 99%
“…The research results from [43] showed that learning tools with problemposing approaches were effective to be applied in scale learning in the fifth-grade elementary school students. Research results from [44] showed that motion graphic media was effective in the learning process. In addition, the results of research from [45] showed that the use of a contextual approach in learning could improve the mathematical representation skills of students with high, medium, and low categories compared to conventional approaches.…”
Section: Resultsmentioning
confidence: 99%